The Consequences of School Dropout in the Kadey Division of Batouri; East Region of Cameroon - Ndjouma Wedjou, Maurice (International Journal of Scientific Research and Management (IJSRM), 2021)
The agenda for sustainable development 2030 has been established and approved by the general assembly of the United Nations in 2015. This agenda includes 17 goals adopted by several countries to promote the development of local communities by tackling and reducing the consequences of school dropout. The continent of Africa through the agenda 2063 endorses different aspirations that have to be met by the year 2063 to minimize the consequences of school dropout, which would lead to a peaceful and protected Africa. The Cameroon Vision 2035 also defined a practical vision of long-term development in the country of Cameroon founded on the eradication of the consequences of school dropout. However, school dropout remains a reality worldwide and generates several consequences which drastically impact the lives of people. It is on this evidence that this research work aimed at exploring the consequences of school dropout in the Kadey Division, East Region of Cameroon.  This study refers to the qualitative research method using the subjectivism ontology and the inductive approach. The epistemology is interpretivism and the axiology is value-bias. The research also employs interviews as the sampling strategy, and 20 respondents gathered in 4 focus groups representing the educational stakeholders of the Kadey Division have volunteered to participate in these interviews. Data were analyzed through the various coding of the grounded theory including open coding, axial coding, and selective coding. The social, education, and economic consequences of school dropout were identified as well. Parents and educators must acknowledge that school failure has this particularity that it penalizes a child for the rest of his life. Any student who stops his studies before having completed his secondary school or vocational training has fewer opportunities to grow within the society. This study recommends that the community stakeholders in the Kadey Division, East region of Cameroon must work collaboratively on minimizing the consequences of school dropout to contribute to the sustainable development of this locality